Relationships are Key : Building Intercultural Capabilities for Indigenous Postgraduate Coursework Students and their Teachers : Final Report of the Project Keeping on Track: Teacher Leaders for Indigenous Postgraduate Coursework Students. - Nobin, Ken; Frawley, Jack; Jackson, Trina; McGinty, Sue; Watkin-Lui, Felecia; White, Nereda (Office for Learning and Teaching, 2013)
In 2008 there were 1527 Indigenous postgraduate students across Australian universities out of a total enrolment of 278,323. This represents approximately 0.54% (DEEWR, 2010) - a clear shortfall against the accepted benchmark of around 3% (IHEAC, 2007). Undoubtedly more needs to be done to recruit Indigenous students into postgraduate programs, and, importantly, these programs need to be designed and taught with special attention to the needs of Indigenous postgraduate students. While there has been significant work in the area of supporting Indigenous researchers and supervisors (Devlin & James, 2007, Laycock et al, 2009), very little research has focused on similar issues for Indigenous students and their teachers within postgraduate coursework programs. This is the final report from a project that addressed this lack of research by focussing on the postgraduate teaching and learning experiences of Indigenous students and their teachers. The project identified and developed a teacher leadership framework consisting of a series of leadership capability statements informed by the data.